2019
DOI: 10.1088/1757-899x/632/1/012060
|View full text |Cite
|
Sign up to set email alerts
|

Method for determining the shock absorber effectiveness in the vehicle suspension to ensure its active and operational safety

Abstract: The article is devoted to the development of a new method for determining the shock absorber effectiveness in the vehicle’s suspension on a vibration stand with vibrating plates, which has greater accuracy and functionality compared to the already known method. The use of the new method will make it possible to reduce the risk of accidents and improve road safety with its widespread introduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Our review of the literature indicated that there are two main approaches on how to evaluate the tribological behavior of hydraulic cylinders. The first one is by mathematical simulation/modeling [16][17][18][19][20], whereas the second one is by developing new lab-scale test procedures [21][22][23][24]. Currently, both approaches have certain limitations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our review of the literature indicated that there are two main approaches on how to evaluate the tribological behavior of hydraulic cylinders. The first one is by mathematical simulation/modeling [16][17][18][19][20], whereas the second one is by developing new lab-scale test procedures [21][22][23][24]. Currently, both approaches have certain limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Lab-scale tests are more applicable for material development, as long as they correlate well with the component behavior. Unfortunately, until now lab-scale tribological tests [21][22][23] focus only on the frictional aspect, which determines the performance of hydraulic cylinders, but not on the wear which dictates the lifetime of this component. Moreover, the lab-scale tests that do measure wear [24] use simplified contacts and different contact geometries that do not closely resemble the actual contact.…”
Section: Introductionmentioning
confidence: 99%